2020
DOI: 10.1039/d0ra03884a
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Cu/chitosan beads as a green and reusable catalyst for facile synthesis of iminesviaoxidative coupling reaction

Abstract: Uniform, spherical Cu/chitosan beads prepared using a software-controlled flow system as a green and conveniently recyclable catalyst for the efficient synthesis of various imines in short reaction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…39 In addition, the peak at 532.79 eV was associated with the oxygen in C−O, which was present in chitosan. 40,41 These XPS results demonstrated that Cu NPs incorporated with chitosan had been triumphantly prepared, which were consistent with the previous analyses.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…39 In addition, the peak at 532.79 eV was associated with the oxygen in C−O, which was present in chitosan. 40,41 These XPS results demonstrated that Cu NPs incorporated with chitosan had been triumphantly prepared, which were consistent with the previous analyses.…”
Section: Resultssupporting
confidence: 90%
“…The peak at 531.21 eV corresponded to the oxygen in O–H, which could be caused by the oxygen chemisorbed on the surface of the nanoparticle . In addition, the peak at 532.79 eV was associated with the oxygen in C–O, which was present in chitosan. , These XPS results demonstrated that Cu NPs incorporated with chitosan had been triumphantly prepared, which were consistent with the previous analyses. For chitosan-coated Cu NPs, chitosan served as a protective agent of nanoparticles, which could prevent Cu NPs from oxidation and aggregation. Compared with the copper oxide nanoparticle (e.g., CuO nanoparticle), Cu NPs could better inhibit the growth of bacteria .…”
Section: Results and Discussionsupporting
confidence: 88%
“…Characterization of CS-Cu(II) catalyst was carried out using various techniques, e.g., scanning electron microscopy (SEM) using a Hitachi S-2500 instrument, Fourier-transform spectroscopy (FTIR) employing KBr disc with a PerkinElmer spectrometer, x-ray diffraction (XRD) using a Bruker D8 Advance diffractometer, and nitrogen adsorption/desorption isotherms and pore size distribution using Quantachrome AUTOSORB-1 system. The results are shown in Supplementary Material A [28].…”
Section: Methods Of Characterization Of Cs-cu(ii) Catalyst Particlesmentioning
confidence: 99%
“…A SEM picture of the micron-size CS-Cu(II) catalyst is shown in Figure S1a, Supplementary Material A [28]. The surface morphology of the particle shows unique streaking patterns with uniform surface structure.…”
Section: Characterization Of Cs-cu(ii) Catalyst Particlesmentioning
confidence: 99%
“…Furthermore, these catalysts are often not recoverable. With this regard, exploration of efficient heterogeneous catalysts including photocatalysts [2g–j,3i,j,4] and transition metal catalysts [2f,n,3c,5] have been reported.…”
Section: Introductionmentioning
confidence: 99%